Theory, the Final Frontier? A Corpus-Based Analysis of the Role of Theory in Psychological Articles - Beller, Sieghard; Bender, Andrea (Frontiers in Psychology, 2017)
Contemporary psychology regards itself as an empirical science, at least in most of its subfields. Theory building and development are often considered critical to the sciences, but the extent to which psychology can be cast in this way is under debate. According to those advocating a strong role of theory, studies should be designed to test hypotheses derived from theories (theory-driven) and ideally should yield findings that stimulate hypothesis formation and theory building (theory-generating). The alternative position values empirical findings over theories as the lasting legacy of science. To investigate which role theory actually plays in current research practice, we analyse references to theory in the complete set of 2,046 articles accepted for publication in Frontiers of Psychology in 2015. This sample of articles, while not representative in the strictest sense, covers a broad range of sub-disciplines, both basic and applied, and a broad range of article types, including research articles, reviews, hypothesis & theory, and commentaries. For the titles, keyword lists, and abstracts in this sample, we conducted a text search for terms related to empiricism and theory, assessed the frequency and scope of usage for six theory-related terms, and analysed their distribution over different article types and subsections of the journal. The results indicate substantially lower frequencies of theoretical than empirical terms, with references to a specific (named) theory in less than 10% of the sample and references to the same theory by more than one article in less than 2%. In conclusion, we discuss possible limitations of our study and the prospect of theoretical advancement.